Taxonomic characterization of ten Thraustochytrids strains isolated from mangrove Xuan Thuy, Nam Dinh - Hà, Nguyễn Thị Hoài; Đào, Phạm Thị Bích; Tuấn, Nguyễn Đình (Vietnam Journal of Biotechnology, 2016)
Thraustochytrids have become of considerable industrial and scientific interest in the past decade due to their health benefits. Thraustochytrids are found in a wide variety of marine habitats such as the coastal, mangrove and sediments including the deep sea. Thraustochytrids are extremely common on the detritus, macroalgae and decaying leaf, they play an important role as organic matter-degrading microorganisms Thraustochytrids are unicellular, eukaryotic, chemo-organotrophic organisms. Ten thraustochytrids strains PT269, PT270, PT273, PT274, PT279, PT284, PT285, PT287, PT81, PT84 were isolated from four locations in Xuan Thuy mangroves, Nam Dinh. In this report, classification is based on morphology and 18S rDNA sequences. Ten Thraustochytrid strains could be classified into three types of colony and four types of cell morphology. Molecular phylogenetic analysis of 18S rDNA sequences showed homology score to be 99-100% and these strains belonged to four genera in the family Thraustochytriaceae. PT269, PT279, PT284 and PT287 strains belong to Aurantiochytrium genus, they produce amoeboid cells and occur successive binary division. PT273 and PT285 strains belong to Thraustochytrium genus, thallus directly develop and cleave into sporangium. PT274 strain belong to Aplanochytrium genus with two distinct development, amoeboid cells are found, they rapidly round up and become sporangium; and successive binary cell division. PT270, PT81 and PT84 strains belong to genus Schizochytrium, they have successive binary cell division, zoospores release.